Manfaat Pentingnya Meningkatkan Literasi Finansial Anak Sekolah Dasar Dengan Program Social Fair And Festival Literasi Finansial Di Kebun Teh Wonosari - Ridwan Mahmud; Budi Prabowo (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2023)
In Indonesia, the financial literacy index is still relatively low, so that financial well-being can increase if financial literacy education is given from elementary school. The purpose of this research is to discuss the importance of increasing financial literacy among elementary school students through exhibitions and social festivals. This research is a descriptive qualitative research. Data collection techniques in this study include interviews, observation, and documentation. The results of this study are that the Festival and Social Fair programs can increase students' understanding of financial literacy as reflected in students' abilities; financial management, transaction execution, simple and autonomous reporting.